Artificial Intelligence Application Assisted Media to Improve Islamic Religious Education Learning Outcomes of Students at SMP Negeri 1 Panti - Yumeldi (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using learning media assisted by Artificial Intelligence. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning media assisted by Artificial Intelligence can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 42.71%, the first cycle 60.39% and in the second cycle it increased to 85.66%. Thus, the use of learning media assisted by Artificial Intelligence can be used as an alternative to improve student learning outcomes in Islamic religious education learning.